Sosialisasi Hasil Uji Aktivitas Gel Ekstrak Daun Sembung Rambat sebagai Solusi Herbal untuk Luka Diabetes - Kusumanti, Yulia; Christiani, Meity; Hasibuan, Ustifina Hasanah (Jurnal Masyarakat Indonesia (Jumas), 2025)
The creeping sembung (Mikania micrantha Kunth.) is classified as a plant in the Asteraceae family and the Angiospermae phylum. Sembung rambat is a plant that has been studied for its various pharmacological effects, including as a coagulant, analgesic, antibacterial, antifungal, anti-inflammatory, anticancer, and antidiabetic. The creeping sembung plant contains active compounds such as alkaloids, flavonoids, tannins, saponins, glycosides, and terpenoids. To determine whether the preparation of ethanol extract of creeping sembung leaves (GEEDSR) can be a diabetic wound healer, this type of research was conducted through experimental research to determine the formulation of a gel preparation containing ethanol extract of creeping sembung. The results obtained by administering gel from formula group 3 provided relatively more effective results in reducing the diameter of the wound with a reduction of ±1.60 cm on day 14. Meanwhile, the gel from formula group 1 was relatively less effective in the reduction process on day 14, namely ±4.95 cm. In this study, cogongrass leaves in gel preparations at a concentration of F3 4.5% provided good results at all concentrations.